Current state of research on acupuncture for acne: a scoping review - Huang, Huiyuan; Liu, Ying; Wu, Shuhui; Zhao, Dan; Zheng, Huie; Zhu, Mingfang (Frontiers in Physiology, 2025)
ObjectiveAcne vulgaris is recognized as one of the top eight most disabling dermatological diseases globally. Acupuncture has emerged as a clinically valuable and widely practiced intervention for acne, with the World Health Organization endorsing it as an effective non-pharmacological treatment. While existing evidence demonstrates acupuncture’s ability to significantly improve acne symptoms, the research remains scattered and lacks comprehensive synthesis. This scoping review systematically maps the current clinical research on acupuncture for acne treatment to identify knowledge gaps and inform future research directions.MethodsA systematic search was conducted across PubMed, EMBASE, the Cochrane Library, Web of Science, AMED, SinoMed, CNKI, WanFang, and VIP databases to identify relevant studies published between January 2014 and October 2024. Data extraction and synthesis were performed using descriptive statistics and visual analytics. The review followed the PRISMA-ScR guidelines and was prospectively registered with the OSF.ResultsThis study included 114 eligible studies, comprising 48 randomized controlled trials, 63 non-randomized interventional studies, and 3 systematic reviews, with the vast majority conducted in China. After 2019, the publication output of acupuncture studies for acne treatment showed a declining trend, which was generally consistent with changes in research funding. Cochrane risk-of-bias assessment revealed that the overall methodological quality of RCTs was moderate, with a low proportion of high-quality studies. The main acupuncture interventions for acne included filiform needle acupuncture, pricking-cupping, fire needling, autohemotherapy, bloodletting therapy, and catgut embedding at acupoints, with Ashi point (local lesion area) being the most frequently selected acupoint. Among the 16 outcome measures evaluated, the effective rate was the most commonly used indicator. Overall, acupuncture demonstrated good safety in treating acne, although fire needling showed a significantly higher frequency of adverse events compared to other therapies.ConclusionAs a globally prevalent complementary therapy, acupuncture has established a substantial research base for acne treatment; however, methodological limitations persist in existing studies. Future research should conduct multicenter, large-sample randomized controlled trials adhering to standardized reporting guidelines, develop comprehensive efficacy evaluation systems incorporating objective indicators, and investigate connections between clinical outcomes and mechanistic pathways. These efforts will elevate the evidence level for acupuncture in acne management.Systematic Review Registrationhttps://doi.org/10.17605/OSF.IO/S2QT6.